Assessment of a feed additive consisting of all‐rac‐alpha tocopheryl acetate (vitamin E) for all animal species for the renewal of its authorisation (EUROPE‐ASIA Import Export GmbH). (28th April 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Fašmon Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of all‐rac‐alpha tocopheryl acetate (vitamin E) as a feed additive for all animal species. The applicant provided data demonstrating that the additive currently in the market complies with the conditions of authorisation. The FEEDAP Panel confirms that the use of all‐rac‐alpha‐tocopheryl acetate under the current authorised conditions of use is safe for the target species, the consumers and the environment. No concern for user safety is expected from the use of the active substance; however, due to the lack of information, the FEEDAP Panel is not able to conclude on its skin sensitisation potential. To draw conclusions on the safety for the user of the final formulated additives, specific studies would be required. There is no need to assess the efficacy of all‐rac‐alpha‐tocopheryl acetate in the context of the renewal of the authorisation.